Ludic and Narrative Immersion in Virtual Reality Exposure Therapy to Animal Phobias: A Systematic Literature Review - Silvino Martins; Mário Vairinhos (Virtual Worlds, 2023)
In the context of therapeutic exposure to phobias, virtual reality (VR) offers innovative ways to motivate patients to confront their fears, an opportunity not feasible in traditional non-digital settings. This systematic literature review explores the utilization of narratives and digital games in this context, focusing on identifying the most common ludic and narrative immersion features employed in studies dedicated to animal phobias. Via a search on the Scopus and Web of Science scientific databases, twenty-nine studies were selected for in-depth analysis. The primary objective was to evaluate the presence of ludic and narrative elements in each study to understand their immersive potential across both dimensions. Findings suggest that ludic elements are more commonly used than narrative elements, which are notably scarce, and the exploration of the emotional dimension of narrative immersion is limited. An essential takeaway is that features fostering narrative immersion are invariably linked to the ludic dimension, often functioning as secondary components. This study provides a guiding framework for developing therapeutic interventions in VR, emphasizing the incorporation of ludic and narrative aspects. Additionally, it identifies untapped research opportunities, particularly the integration of autonomous narratives that are less reliant on ludic elements.